Real-time and Multi-physics Fiber Optic Monitoring of Landslides in Three Gorges Reservoir Area. Issue 4 (October 2021) - Zhu, H-H; Ye, X; Pei, H F; Cheng, G; Zhang, W; Wang, J; Shi, B
Abstract: Accurate and real-time measurement of the evolution of landslides has become a great concern in recent years. Fiber Bragg grating (FBG), as a popular quasi-distributed fiber optic sensing technology, has been successfully applied to geotechnical and geohazard monitoring. In this paper, an FBG-based real-time monitoring system has been developed to capture the multi-physics evolution of creeping landslides. The system was employed to monitor the performance of the Majiagou and Xinpu landslides in the Three Gorges Reservoir (TGR) area of China, respectively. The results show that the FBG monitoring system can accurately obtain the variations of ground temperature, soil moisture, and deep displacements, which provides valuable information for evaluating the landslide deformation and failure mechanisms during the operation of the reservoir. In this way, real-time stability analysis and early warning can be achieved.